Prevalence of Mental Health Problems and Its Associated Factors Among Recovered COVID-19 Patients During the Pandemic: A Single-Center Study - Khademi, Mojgan; Vaziri-Harami, Roya; Shams, Jamal (Frontiers in Psychiatry, 2021)
Introduction: The coronavirus disease 2019 (COVID-19), is profoundly affecting the mental health status. Although the burden of mental health problems has been reported in the general population and health care workers, little is known about the prevalence of mental health disorders among recovered COVID-19 patients and their associated factors. Methods: A cross-sectional telephonic-study of recovered COVID-19 patients with and without a history of hospitalization was conducted from April 20 to June 20, 2020, in Tehran, Iran. We assessed the anxiety symptoms, depression, and post-traumatic stress disorder (PTSD) among participants, using the Patient Health Questionnaire (PHQ-4) and PTSD checklist for DSM-5 (PCL-5). Multivariable logistic regression analyses were used to explore the risk factors associated with mental health problems. Results: A total of 602 individuals with a mean age of 53.2 years (SD: 14.7), completed the study. During the COVID-19 pandemic, the rates of mental health symptoms among the respondents were 5.8% (95%CI: 4.2 to 7.8%) for anxiety, 5.0% (95%CI: 3.5 to 7.0%) for depression, and 3.8% (95%CI: 2.3 to 5.3%) for PTSD disorders. Moreover, being younger than 50 years and female gender was significantly associated with a higher probability of reporting anxiety (p<0.01), and depression (p<0.001 for being younger than 50 years, p<0.02 for female gender). Conclusions: The current study indicated that patients with COVID-19 presented features of anxiety, depression, and PTSD. These results may help in implementing appropriate mental health intervention policies for those who are at risk and for minimizing the mental health consequences of the COVID-19 pandemic.